PENGEMBANGAN BAHAN AJARSISTEM PERSAMAAN LINEAR DUA VARIABEL BERBASIS WEBSITEUNTUK MEMBELAJARKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Nur Jakiah; Marzuki Ahmad; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This development research aims to 1) Knowing the validity of developing website-based two-variable linear equation system teaching materials, 2) Knowing the practicality of using web-based two-variable linear equation system development teaching materials in learning activities, and 3) Knowing the effectiveness of developing linear equation system teaching materials two website-based variables to teach students' mathematical problem solving skills. This research is a Research and Development (R&D) research with the ADDIE development model, where this research consists of 5 stages, namely, 1) Analysis Phase, 2) Design Phase, 3) Development Phase, 4) Implementation Phase and 5) Evaluation Phase. The instruments used include 1) a questionnaire sheet in the form of a validation questionnaire by an expert to see the validity of the product and student response questionnaires to see the practicality of the product, as well as 2) a test sheet to test the effectiveness of the developed product being tested on 24 students in class X MIA 1 SMA N 1 Angkola East. Based on the results of this study, the product validity was obtained with an average percentage of 92.61% in the "Very Valid" category, product practicality with an average percentage of 85,52% in the "Very Practical" category, and product effectiveness with an average percentage of 76 ,62% with the category "Effective".It can be concluded that the development of website-based two-variable linear equation system teaching materials to teach students' mathematical problem solving skills is valid, practical and effective. Keywords: Development, Teaching Materials, Problem Solving Ability